2010
DOI: 10.1136/bmj.c6325
|View full text |Cite
|
Sign up to set email alerts
|

Integrated motivational interviewing and cognitive behavioural therapy for people with psychosis and comorbid substance misuse: randomised controlled trial

Abstract: Objectives To evaluate the effectiveness of integrated motivational interviewing and cognitive behavioural therapy in addition to standard care for patients with psychosis and a comorbid substance use problem.Design Two centre, open, rater blind randomised controlled trial.Setting Secondary care in the United Kingdom.Participants 327 patients with a clinical diagnosis of schizophrenia, schizophreniform disorder, or schizoaffective disorder and a diagnosis of dependence on or misuse of drugs, alcohol, or both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(150 citation statements)
references
References 42 publications
4
143
1
2
Order By: Relevance
“…The distinction between treatment-emergent reactions linked to the treatment and unwanted events unrelated to the treatment is central. A few reports in the present review indicated that such judgments were made, in some cases by an Institutional Review Board [27] or an independent Data Monitoring Committee [25].…”
Section: Accepted M Manuscriptmentioning
confidence: 83%
See 1 more Smart Citation
“…The distinction between treatment-emergent reactions linked to the treatment and unwanted events unrelated to the treatment is central. A few reports in the present review indicated that such judgments were made, in some cases by an Institutional Review Board [27] or an independent Data Monitoring Committee [25].…”
Section: Accepted M Manuscriptmentioning
confidence: 83%
“…Five trials provided information about adverse events in the results section but had missing or incomplete information about how the data was collected [24][25][26][27], or how the adverse events were defined [28]. Four reports only briefly stated in the results section [29], methods section [30,31] or the discussion [32] that no adverse events occurred or were observed, without providing information about how these adverse events were defined or monitored.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…21 The intervention being evaluated was a combination of motivational interviewing and cognitive therapy to improve psychotic symptoms in dual-diagnosis patients (a combination of psychosis and substance abuse). In cannabis users, for example, the aim was to test whether or not the intervention reduced cannabis use, which, in turn, would lead to reduction in psychotic symptoms.…”
Section: Putative Mediatorsmentioning
confidence: 99%
“…For example, in the MRC MIDAS trial, 21 the putative mediator was substance misuse, and this was measured at baseline and at 6, 12, 18 and 24 months after baseline. The corresponding outcome measures of psychotic symptoms were collected at baseline and at 12 and 24 months.…”
Section: Introductionmentioning
confidence: 99%
“…Here, mixed results have been reported. Some studies have found results favouring the MI-enhanced treatments relative to standard care for substance abstinence rates, 27,63 reduction in substance use, 21,64 and psychiatric symptom improvement, 27,65 whereas others have reported no significant group differences on these indices. 31,66 In addition, RCTs have generally supported the use of integrated MI interventions in enhancing adherence to antipsychotics among patients with schizophrenia spectrum disorders.…”
Section: For Dual Diagnosismentioning
confidence: 99%